Fracture criterion for ice using a dislocation model - Parameswaran, V. R. (1982)
The propensity for crack formation on basal and prismatic planes and twin nucleation on two pyramidal planes in hexagonal ice is examined on the basis of fracture theories and anisotropic elastic theories of dislocations. Calculations show that the ease of crack formation is almost the same in the basal and prismatic planes, whereas it is almost impossible to produce mechanical twinning in ice by stress alone. Sur la base des théories de la fracture et des théories élastiques anisotropiques des dislocations on examine les possibilités pour la formation de fissures sur les plans de base et sur les faces pyramidales ainsi que la nucléation des macles sur deux faces pyramidales dans de la glace hexagonale. Les calculs montrent que la formation de fissure est presque aussi facile sur le plan de base et sur les faces prismatiques, alors qu'il est presque impossible de produire des macles dans la glace par le seul exercice d'un effort mécanique. Peer reviewed: Yes NRC publication: Yes